Pelatihan Pembelajaran Numerasi Berdiferensiasi Menggunakan Media Digital bagi Guru Sekolah Dasar Luar Biasa (SDLB) - Lutfianto, Moch.; Lestariningsih, Lestariningsih; Hartanto, Wido (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
The challenges faced by teachers, ranging from the diverse cognitive abilities of each student to unique learning styles, cause the numeracy learning process in Special Elementary Schools (SDLB) to become increasingly complex. Meanwhile, several studies and discussion results show that teachers' ability to design differentiated numeracy learning using digital media is still low. Hence, community service was carried out with the aim of developing the abilities of SDLB teachers in designing differentiated numeracy learning using digital media for teachers at SDLB Muhammadiyah in Gresik. Service activities start from preparation, socialization, training, application of technology, to mentoring and evaluation. The training activity was carried out for three days at school, and at the end of the activity, participants were asked to fill out an activity questionnaire. Based on the results of activity questionnaires and interviews with teachers, it can be seen that teachers' knowledge in differentiated numeracy learning is developing well. They design differentiated learning based on the results of the initial assessment given to students. Furthermore, teachers' skills in using digital media have also increased. Therefore, we can conclude that this service activity can enhance teachers' skills in designing differentiated numeracy learning through the use of 3D flipbook digital media.